2007
DOI: 10.1080/09540260701278903
|View full text |Cite
|
Sign up to set email alerts
|

Stigma towards people with mental illness in developing countries in Asia

Abstract: This review revealed that the stigmatization of people with mental illness is widespread in Asia. The features of stigmatization-beliefs about causes of and attitudes towards mental illness, consequences for help-seeking-have more commonalities than differences to Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
317
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(345 citation statements)
references
References 224 publications
21
317
3
4
Order By: Relevance
“…Commenting on developing nations in Asia, Lauber and Rossler (2006) noted that stigmatization is more prevalent in these cultures than in Western cultures (47). Kermode et al (2009) found that the majority of participants from his study in rural Maharashtra did not conceptualise depression or psychosis as a "real medical issue" (38) .…”
Section: Predictors Of Depressionmentioning
confidence: 98%
“…Commenting on developing nations in Asia, Lauber and Rossler (2006) noted that stigmatization is more prevalent in these cultures than in Western cultures (47). Kermode et al (2009) found that the majority of participants from his study in rural Maharashtra did not conceptualise depression or psychosis as a "real medical issue" (38) .…”
Section: Predictors Of Depressionmentioning
confidence: 98%
“…Although stigmatization and its effects on mental health help-seeking behavior s are not unique to Filipinos (Abdullah & Brown, 2011;Lauber & Rössler, 2007), hiya could be a potential barrier or a compounding problem to seeking mental health services. Hiya has been loosely translated by some scholars as 'shame'.…”
Section: Public and Private Stigma Hiya And Loss Of Facementioning
confidence: 99%
“…Mental illnesses are amongst the conditions that are most profoundly affected by disease-associated stigma -indeed, it has been suggested that for some affected individuals, the effects of mental illness-related stigma are so negative that they actually often outweigh the negative effects of the illness itself (Hinshaw and Stier 2008). Stigma is a complex social construct comprising interrelated processes that operate at the level of institutions (institutional stigma), social groups (public stigma), and the individual (internalized or self-stigma) (Corrigan and Watson 2002;Hinshaw and Stier, 2008;Lauber and Rossler 2007;Link et al 2004). Of the three levels at which stigma operates, public stigma (defined as the phenomenon whereby large social groups have negative attitudes towards and beliefs about, and even act against those with a disenfranchised trait -like mental illness (Corrigan and Watson 2002)) has received the greatest attention.…”
Section: Introductionmentioning
confidence: 99%
“…Public stigma can have damaging effects for people with mental illness. For example, negative attitudes of mental health workers and psychiatrists towards individuals with mental illness has been associated with decreased use of needed healthcare services amongst individuals with mental illness, thus exacerbating the effects and symptoms of the illness on the individual (Lauber and Rossler 2007;Nordt et al 2006;Rusch et al 2005). …”
Section: Introductionmentioning
confidence: 99%